Entertainment (Read Only) > Post-Based Games/Threads
Let the flame war begin
Alex Mason, SOG:
--- Quote from: Xrain on April 15, 2011, 02:09:41 PM ---Not quite, your making several algebra mistakes.
first you cannot divide items in the denominator separately
But you are correct, multiplication and division have the same priority.
However, it's not order of operations that prevents you from doing this, its the basic rules of algebra that prevents you from calculating it like that.
Unless of course the OP wrote the equation ambiguously intentionally, using a little loop hole in standard equation writing.
48÷2(9+3) Generally means 48/(2*(9+3))
48÷2*(9+3) Can mean
48/(2*(9+3))
or
(48/2)*(9*3)
If that is the case, then it's just a failure on the OP's part to properly define an equation.
If he did intentionally write it that way, He is going to end up banned because stuff like that pisses me off O:-)
If you want something to really mess with your brain, try this on for size.
a=b
ab=b²
ab-a²=b²-a²
a(b-a)=(b+a)(b-a)
a=b+a
a=a+a
1=2
--- End quote ---
I'll ask my teacher tomorrow. Google still agrees with me.....
http://lmgtfy.com/?q=48%2F2(9%2B3)
lets solve the red part, shall we?
(b+a)(b-a)
b*b =b2
b*-a =-ab
a*b =ab
a*-a = -a2
b2-ab+ab-a2
b2-a2
You didn't factor right.....
Xrain:
--- Quote from: bunnykilla on April 15, 2011, 05:16:40 PM ---I'll ask my teacher tomorrow. Google still agrees with me.....
http://lmgtfy.com/?q=48%2F2(9%2B3)
lets solve the red part, shall we?
(b+a)(b-a)
b*b =b2
b*-a =-ab
a*b =ab
a*-a = -a2
b2-ab+ab-a2
b2-a2
You didn't factor right.....
--- End quote ---
Aha! the key is you don't factor at all, just divide both sides by (b-a)
a(b-a)=(a+b)(b-a)
a(b-a)/(b-a)=((a+b)(b-a))/(b-a)
a=a+b
Don't get me wrong there is something horribly wrong with that proof, I'm just curious to see if you can find it. ;D
Alex Mason, SOG:
woops you did factor right (or divide, looks like factoring to me)
lets start replacing variables.
a=b kgood
ab=b² aa=a2 0=0
a2=a2 0=0
ab-a²=b²-a² aa-a2=a2-a2 0=0
a(b-a)=(b+a)(b-a) a(a-a)=(a+a)(a-a)
a(0)=(2a)(0) 0=0
a=b+a ........ after replacing variable this makes NO sense, but I cant really explain it.
a=a+a
1=2
Xrain, I hate you. You confuse me too much. :(
Shawn:
--- Quote from: Shawn on April 13, 2011, 08:02:40 PM ---BEDMAS
48÷2(9+3)
=
48/2(12)
=
48/24
=
2
Therefore the answer is 2.
--- End quote ---
FUCK i failed forgot to / first :(
48÷2(9+3)
=
48/2(12)
=
24x12
=
288
And 288 is the correct answer For those of you using a calculator and getting a different answer is because its not a scientific one
Wafflepiezz:
This is interesting :3
Navigation
[0] Message Index
[#] Next page
[*] Previous page
Go to full version